Announcement of Retraction - Eva Nurlita; Robiyanto Robiyanto (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2021)
Retraction to:Article Title:   The Effect of Financial Performance And Company Size On Sharia Stock Listed                In Jakarta Islamic IndexAuthors: Eva Nurlita, Robiyanto Robiyanto This article has been retracted by the publisher based on the following reason This is based on the author's recognition to the editor that the author admits that he forgot to have submitted the same article to another journal.